Graphene‐Like Monoelemental 2D Materials for Perovskite Solar Cells. Issue 12 (12th February 2023) - Suragtkhuu, Selengesuren; Sunderiya, Suvdanchimeg; Myagmarsereejid, Purevlkham; Purevdorj, Solongo; Bati, Abdulaziz S. R.; Bold, Bujinlkham; Zhong, Yu Lin; Davaasambuu, Sarangerel; Batmunkh, Munkhbayar
Abstract: Perovskite solar cells (PSCs) have attracted a great deal of attention from the photovoltaic (PV) community because of their remarkable performance, low production cost, and high potential to be integrated into other optoelectronic applications. Despite their promise, the challenges associated with their operational stability have drawn increasing attention over the past decade. Owing to their unique structure and fascinating properties such as high charge mobility, excellent conductivity, tunable bandgap, good optical transparency, and optimal surface functionalization, nanostructured materials, in particular monoelemental 2D materials, have recently been demonstrated to play versatile functions in suppressing the degradation of PSCs and enhancing the PV performance of the devices. In this review, recent advances in perovskite solar cells employing monoelemental 2D materials are presented. A brief overview of perovskite light absorbers based PV devices is first introduced, followed by critical discussions on the use of various elemental 2D materials including graphene, phosphorene, antimonene, borophene, bismuthene, and their derivatives for different components of the perovskite solar cells. Finally, the challenges in this cutting‐edge research area are highlighted, and the authors express their own perspectives on addressing these key issues. Abstract : Monoelemental 2D materials exhibit a broad range of fascinating properties. Thickness‐dependent bandgap is their most defined and controllable property, making them attractive for photovoltaic applications. This review outlines the recent advancements and notable achievements of perovskite solar cells employing monoelemental 2D materials.